VALIDATING ONLINE TEACHING MATERIALS OF CORPUS LINGUISTICS - Wan Nazihah Wan Mohamed; Anis Idayu Aziz; Nor Hairunnisa Mohammad Nor (Journal of Islamic, Social, Economics and Development, 2023)
Fourth Industrial Revolution or known as 4th IR marks numerous changes to the way we live, work, and connect with one another as we implement smart technologies in accomplishing our mission in life. This revolution has given a big impact to all disciplines, industries and economies. Thus, in supporting the transmission of industrial revolution and education 5.0, many educators are continuously putting their effort in creating and designing effective instructional methods to boost the process of teaching and learning. To fit the current mobile educational setting, educators especially at higher educational institutions (HIEs) expose their learners with online learning materials that aim to achieve the main learning objectives. Despite the growing establishment of developing and designing online teaching materials, there is a big question on how the contents of online English teaching materials are being validated. Therefore, this paper provides a contextualised exploration on the use of corpus linguistics in supporting the development of online teaching materials.